(untitled) (The International Journal for Scientific Research, 2026)
This research examines the legal theory of unforeseen circumstances (hardship doctrine) as a mechanism for balancing contractual binding force against the demands of contractual justice. The theory applies when exceptional, unforeseeable general events arise after a contract is concluded, making performance excessively burdensome for the obligor without rendering it entirely impossible. The study traces the theory’s jurisprudential roots in Islamic law through concepts such as jawā’iḥ (crop disasters) and ’udhr (legal excuse), supported by general legal maxims such as "harm must be removed" and "hardship invites ease." It then analyzes how the theory was codified in the Saudi Civil Transactions Law (1444H/2022), particularly Article 97, which grants the debtor the right to invite renegotiation and empowers courts to reduce an onerous obligation to a reasonable limit. The research distinguishes the theory from force majeure in terms of conditions, effects, and legal consequences, and examines judicial applications in construction contracts and commercial lease disputes during the COVID-19 pandemic, finding a clear judicial preference for preserving contracts through rebalancing rather than termination. The study concludes that Saudi law has successfully institutionalized the theory, while recommending the development of clearer judicial standards for "excessive hardship" and greater consistency in judicial reasoning.